All‐cause and diabetes‐related healthcare costs among US adults with type 2 diabetes initiating exenatide once weekly or insulin glargine. Issue 3 (26th November 2017) - Wittbrodt, Eric; Kong, Amanda M.; Moore‐Schiltz, Laura; Juneau, Paul
Abstract : Aims: To compare healthcare utilization and costs between patients with type 2 diabetes (T2D) treated with exenatide (Bydureon) once weekly (EQW) and patients treated with insulin glargine (IG). Materials and methods: Using the MarketScan Commercial and Medicare Supplemental databases, we conducted a retrospective cohort study of adult US patients with claim with a diagnosis of T2D, initiating EQW or IG from February 1, 2012 to June 30, 2014 (first claim = index date). All‐cause and diabetes‐related utilization and costs were measured during the 12 months after the index date. EQW patients were matched 1:1 to IG patients, using propensity scores. Logistic and ordinary least‐squares regression models were fit to model differences between the matched cohorts. Results: There were 7749 EQW patients matched to 7749 IG patients. EQW patients had significantly ( P  < .05 ) lower odds of all‐cause inpatient (IP) admissions (odds ratio = 0.737 [95% confidence interval, 0.661, 0.822]), diabetes‐related IP admissions (0.720 [95% confidence interval, 0.635, 0.815]) and diabetes‐related IP admissions or emergency room visits (0.778 [95% confidence interval, 0.713, 0.847]). EQW patients had significantly ( P  < .05) lower all‐cause (cost difference = −113 USD [95% confidence interval, −120 USD, −106 USD]) and diabetes‐related (−806 USD [95% confidence interval, −871 USD, −746 USD]) medical costs, and had significantly ( P  < .05) higher all‐cause total costs (ie, medical plus pharmacy) (3228 USD [95% confidence interval, 3110 USD, 3367 USD]), diabetes‐related total costs (1951 USD [95% confidence interval, 1873 USD, 2036 USD]), all‐cause pharmacy costs (2792 USD [95% confidence interval, 2700 USD, 2928 USD]) and diabetes‐related pharmacy costs (1923 USD [95% confidence interval, 1890 USD, 1957 USD]) than those of IG patients. Conclusions: Among adults with T2D, EQW initiators had lower odds of IP admission and lower medical costs in the 12 months after initiation than IG initiators. Higher total costs in EQW patients were driven by greater pharmacy costs.